RISKS OF EXPOSURE TO VETERINARY MARBOFLOXACIN RESIDUES THROUGH MILK - Doaa H. Abdulrazzaq,; Sawsan M. Amin,; Mohammad K. Shindala, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
The veterinary antibacterial Marbofloxacin (Marbo) is used in food-producing animals, including dairy cows, so the residues of this drug will be excreted through milk. This study was aimed to investigate  a risk of developmental and  neurobehavioral toxicity effects in newborn consumers exposed to the residues of this drug. To achieve this goal, suckling pups of  rats were selected as a model. Four groups of female lactating rats (5 dams for each group – 8 pups per dams) were divided into (A,B,C,D) treated with Marbo (0 (control) , 3, 6 ,9 mg/kg, i.m.) given once daily for 10 consecutive days (first nursing period) respectively.The exposure of suckling pups to the drug through milk in group (D) led to neurobehavioral toxicity effects represented in the occurrence of a significantly prolongation in both the time required to terminate the surface righting reflex on postnatal day (PND) 5 and the time of induction and duration of anesthesia by (ketamine and xylazine) on the  (PND) 21 . the newborns in group (C) recorded a significantly prolongation of both in the period of appearance of pinna detachment and in induction and duration of anesthesia accompanied by a significantly decrease in numbers of squares crossed  in open field activity test on the  (PND) 21 .It could be conclude from our current study that there are risks of causing developmental and neurobehavioral toxic effects in newborn consumers exposed to Marbo residue in animal products such as milk.